1995
DOI: 10.1002/jcp.1041640112
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of leukemia inhibitory factor to murine myoblasts in culture

Abstract: Leukemia inhibitory factor (LIF) is a member of the cytokine family of growth factors. It has been shown to exert a variety of actions on a diverse range of cell types, including neuronal, bone, and hemopoietic cells (Hilton, 1992, Trends Biochem. Sci., 17:72-76). In many of these cell types, studies have indicated the presence of specific receptors for LIF (Godard et al., 1982, J. Biol. Chem., 267: 3214-3222; Hilton et al., Proc. Natl. Acad. Sci. USA, 85:5971-5975; Hilton and Nicola, 1992, J. Biol. Chem., 267… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In pituitary cells, protein-tyrosine phosphatases SHP1 and SHP2, and SOCS3, are proposed to down-regulate LIF signaling within 30 min to 1 h by inactivation of JAK2 and/or STAT3 (18 -21, 33). In myoblasts, it is also suggested that a separate mechanism operates via down-regulation of the LIFR␣ protein (9). To test the latter possibility, we measured the level of immunodetectable LIFR␣ after LIF treatment in the rat hepatoma cell line H-35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pituitary cells, protein-tyrosine phosphatases SHP1 and SHP2, and SOCS3, are proposed to down-regulate LIF signaling within 30 min to 1 h by inactivation of JAK2 and/or STAT3 (18 -21, 33). In myoblasts, it is also suggested that a separate mechanism operates via down-regulation of the LIFR␣ protein (9). To test the latter possibility, we measured the level of immunodetectable LIFR␣ after LIF treatment in the rat hepatoma cell line H-35.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, during the acute phase reaction, insulin is increased 3-fold (6) and then modulates the cytokine regulation of APP genes (7,8). In myoblasts, IGF-1 also reduces LIF action, apparently by down-regulating LIF receptor number (9).…”
mentioning
confidence: 99%
“…However, both mRNAs were apparently downregulated in the newly formed myotubes. There are many data showing that LIF is upregulated in regenerating myofibers and that this contributes to the proliferation of myoblasts in vitro (Austin et al 1992;Barnard et al 1994;Bower et al 1995;Kami and Senba 1998). The complex of gp130 and LIFR is also utilized as a signal transducer to mediate the biological actions of CNTF, OM, and CT-1 (Kishimoto et al 1994), but there are no reports suggesting the synthesis of these cytokines in regenerating muscles or their roles in myogenesis in vivo or in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Because the density of high-affinity receptors on LIF-responsive cells is relatively low, with an average of 300 binding sites per cell (Godard et al, 1992;Tomida, 2000), LIF binding is a low-capacity process that may readily become saturated. Following receptor binding, the entire LIF-receptor complex is subject to internalization and degradation by lysosomal enzymes (Bower et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The collective processes of internalization, intracellular transport, and lysosomal degradation are characterized by a first-order rate constant, k int . Because in vitro studies have demonstrated that the LIF receptor is degraded within the cell, a receptor recycling component is not required in this model (Bower et al, 1995).…”
Section: Methodsmentioning
confidence: 99%